2014
DOI: 10.1371/journal.pone.0087614
|View full text |Cite
|
Sign up to set email alerts
|

Colonic miRNA Expression/Secretion, Regulated by Intestinal Epithelial PepT1, Plays an Important Role in Cell-to-Cell Communication during Colitis

Abstract: PepT1 is a member of the proton-oligopeptide cotransporter family SLC15, which mediates the transport of di/tripeptides from intestinal lumen into epithelial cells. MicroRNAs (miRNAs), a small noncoding RNAs (21–23 nucleotides), post-transcriptionally regulate gene expression by binding to the 3′-untranslated regions (UTRs) of their target mRNAs. Although the role of most miRNAs remains elusive, they have been implicated in vital cellular functions such as intestinal epithelial cells differentiation, prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…After intracolonic treatment with the different above mentioned conditions (B), colonic PepT1 expression was determined by Western blotting and immunofluorescent staining (C). Scale bars ϭ 50 m. recent study, overexpression of colonic PepT1 was found to alter the profile of local miRNA expression/secretion in both epithelial and non-epithelial cells such as intestinal macrophages in a tissue-specific manner (35). Our observation of the dysregulated PepT1 in the colon tissues from active IBD patients is consistent with the previous studies of PepT1 involvement in aggravation of intestinal inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…After intracolonic treatment with the different above mentioned conditions (B), colonic PepT1 expression was determined by Western blotting and immunofluorescent staining (C). Scale bars ϭ 50 m. recent study, overexpression of colonic PepT1 was found to alter the profile of local miRNA expression/secretion in both epithelial and non-epithelial cells such as intestinal macrophages in a tissue-specific manner (35). Our observation of the dysregulated PepT1 in the colon tissues from active IBD patients is consistent with the previous studies of PepT1 involvement in aggravation of intestinal inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…The expression of PepT1 regulates the expression/secretion of specific microRNAs (miRNAs), to thereby regulate the expression levels of multiple proteins27. Intestinal miRNA expression is essential for maintaining intestinal homeostasis.…”
mentioning
confidence: 99%
“…Bacterial MDP has been shown to be transported by intestinal oligopeptide transporter 1 (PepT1) in epithelial cells, which can significantly induce inflammatory responses in animal intestines. Upon the PepT1-mediated transport in intestinal epithelial cells, MDP could be further recognized by the intracellular nucleotide-binding oligomerization domain 2 (NOD2) protein and then by activated receptor-interacting serine/threonineprotein kinase 2 (RIP2) to induce the production of inflammatory cytokines that participate in the intestinal immune response (37,38). Over the past several years, much progress has been made in understanding the immune function of the PepT1-NOD2/RIP2 pathway in bacterial MDP-induced intestinal inflammation in vertebrates (39,40).…”
Section: Discussionmentioning
confidence: 99%